Pengoreksi Nada Menggunakan Mikrokontroler untuk Meningkatkan Kualitas Suara pada Biola - Danu Kusuma Wardhana; Tri Kuntoro Priyambodo (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2016)
Violin is a frteless musical instrument so that carefulness of the player affects the tone quality. For begineers, it tooks a lot of time for fingering process, so if they are not skillfull enough it will generate many out-of-tune pitches which uncomfortable to be heard. For clearing this issue, it needs an equipment for generating in-tune pitches while the violinist is playing-live.System is made using sound sensor for receiving the wave of the violin, turned it out to electric signal and then detecting its pitch value – reading it as the interval of the main frequency – and then playing desired in-tune audio data of violin tones. The main process is done by microcontroller supported by audio shield. The output is in-tune audio data which played through speaker.System achieved 100% accuracy while using pure sinusoid wave tones for testing. System achieved  17,33% accuracy while  using pre-recorded violin tones for testing. System achieved 10,66% accuracy while using live-played violin tones for testing.